Israel : Technical Note on Stress Test of the Banking, Insurance and Pension Sectors. (IMF Staff Country Reports; Country Report ;, 2012)
A technical note on the stress test of Israel's banking, insurance, and pension sectors is presented. The Israel Financial Sector Assessment Program Update stress testing exercise comprises a comprehensive analysis of solvency and liquidity risks of key banking and insurance institutions. Satellite models cover housing and corporate credit, household nonhousing credit, profit components, profit retention behavior, and haircut models of government and financial institution bonds. Single-factor tests have been conducted to estimate vulnerabilities to market risk and an idiosyncratic credit shock from exposures to the largest borrower groups and the three largest corporate borrowers.